PEMETAAN PERSEBARAN RUMAH TANGGA PENERIMA PKH DI KELURAHAN PARAK LAWEH KECAMATAN LUBUK BEGALUNG - Nurul Oktimawani Tanjung; Ratna Wilis (JURNAL BUANA, 2021)
This research was conducted in Parak Laweh Village which aims to see the condition of PKH recipient households and see the effectiveness of PKH distribution and see how the distribution of PKH recipients is. The method used in this research is descriptive quantitative approach and the data used are primary data. The results of the study were obtained from the results of interviews and questionnaires and taking the coordinate points. The condition of PKH recipient households, from 1565 households, only 132 received PKH. The effectiveness of PKH recipients is lacking effectiveness because the distribution is uneven and the data collection is not good and the distribution pattern of PKH recipient distribution in Parak Laweh Village is centered / close. The number of PKH recipients in each jorong is very small based on the number of poor families and the number of families owned by each RW. The large number of households in a RW will affect the number of PKH recipient families found in the RW.